2018
DOI: 10.1007/s40477-018-0346-x
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced ultrasound (CEUS) in pediatric blunt abdominal trauma

Abstract: Baseline ultrasound is the first-choice technique in traumatic hemodynamically stable children, and is essential in the early assessment of unstable patients to detect hemoperitoneum or other potentially fatal conditions. Despite the technological advancements in new ultrasound equipment and the experience of the operators, it is not always possible to rule out the presence of parenchymal traumatic lesions by means of baseline ultrasound nor to suspect them, especially in the absence of hemoperitoneum. For thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 69 publications
0
15
0
8
Order By: Relevance
“…UCAs are generally well tolerated; the rate of adverse reactions is very low (1:7000 patients, 0.014%). This rate is significantly lower than the rate associated with iodinated state-of-the-art CT agents (35-95:100 000 patients, 0.035-0.095 %) [10,13]. The main contraindications for UCAs are a history of allergic reactions to the contrast agent, severe pulmonary hypertension, severe coronary artery disease, pulmonary hypertension, and unstable ischemic heart disease.…”
Section: Ultrasound Contrast Agentmentioning
confidence: 90%
See 1 more Smart Citation
“…UCAs are generally well tolerated; the rate of adverse reactions is very low (1:7000 patients, 0.014%). This rate is significantly lower than the rate associated with iodinated state-of-the-art CT agents (35-95:100 000 patients, 0.035-0.095 %) [10,13]. The main contraindications for UCAs are a history of allergic reactions to the contrast agent, severe pulmonary hypertension, severe coronary artery disease, pulmonary hypertension, and unstable ischemic heart disease.…”
Section: Ultrasound Contrast Agentmentioning
confidence: 90%
“…The main contraindications for UCAs are a history of allergic reactions to the contrast agent, severe pulmonary hypertension, severe coronary artery disease, pulmonary hypertension, and unstable ischemic heart disease. The use of UCAs is not authorized for pregnant or breastfeeding women [10,13]. The use of UCAs is yet to be off-label for children; however, there is a large consensus on their safety [10,14] 2.1.3.…”
Section: Ultrasound Contrast Agentmentioning
confidence: 99%
“…Since the contrast agent is breathed out by the lungs (laboratory testing prior to examination (i. e. kidney function) not required) and there is no ionizing radiation, CEUS is much more suited for initial examination as well as for follow-ups in trauma with conservative management in the pediatric patient [31]. However, the second-generation contrast agents are still off-label in children although several multi-centric studies have already demonstrated safety in pediatric populations [32,33].…”
Section: Diagnosismentioning
confidence: 99%
“…A fundamental practical approach is described in the EFSUMB Guidelines [10][11][12]. CEUS application in children is currently still "off-label" except for a few indications including vesico-uereteral reflux, but it could be a very useful method in the non-ionizing imaging of young patients [6,[13][14][15][16][17]. Today, in the emergency setting, CEUS is used predominantly in the study of blunt or penetrating traumatic lesions, especially for the diagnosis and follow-up of the solid parenchymal organ (socalled "non-operative management") [8,[18][19][20][21][22].…”
Section: A B C Dmentioning
confidence: 99%
“…A fundamental practical approach is described in the EFSUMB Guidelines 10 11 12 . CEUS application in children is currently still “off-label” except for a few indications including vesico-uereteral reflux, but it could be a very useful method in the non-ionizing imaging of young patients 6 13 14 15 16 17 .…”
Section: Manuscriptmentioning
confidence: 99%